A rare occurrence of Serratia rubidaea in a patient with ear discharge - Vimal Kumar Karnaker; Asem Ali Ashraf; Sreelatha Shankaran Veetil; Bhavya Chand; Sanjana Nair; Sudhir Rama Varma (Elsevier, 2023)
Serratia species are not as frequent as with more virulent members of the Enterobacteriaceae. However, when infections do arise, they are largely associated with Serratia marcescens. Presently, about 10 species of Serratia are recognized and infections caused by the remaining Serratia species are seldom recorded in literature, as they are not often isolated from clinical specimens. This is a case report of Serratia rubidaea isolated from ear discharge of a 35-year old female patient with no co-morbidities and with known history of chronic otomastoiditis for which the patient had undergone left modified radical mastoidectomy. Isolation of this bacterium from clinical specimens is rare; however, it can be an etiological agent for infections in patients who have undergone invasive procedures. The patient was managed with antibiotics and on otoendoscopy at follow-up, no discharge was observed.